The Effect Of Strategic Orientation And Business Model Innovation On Financial Performance: The Case Of Ikat Weaving SMEs In Bali - Susanti Christina; Wiryanata I Gusti Ngurah Agung (SHS Web of Conferences)
This study investigates the impact of strategic orientation and business model innovation on financial performance. A questionnaire was distributed to gather data from 51 managers of ikat weaving SMEs in Bali Province, and partial least squares structural equation modeling (PLS-SEM) was used to evaluate the hypotheses. The results showed that business model innovation completely mediates the relationship between strategic orientation and the financial performance of SMEs, with strategic orientation having a positive and significant influence on both variables. This research builds on existing studies related to the financial performance of SMEs, business model innovation, and strategic orientation. The findings provide valuable guidance for SME managers in developing strategies and testing innovative business models, which can improve financial performance and help them make informed decisions to advance their enterprises.